أثر الاهتلاك بالمركبات على الأداء المالي لمؤسسة هيبروك: The impact of component depreciationon the financial performance of the Hiproc Corporation - سيد علي حسين; جميلة الجوزي (Journal of North African Economies, 2025)
This study aims to identify the effect of component depreciation on the financial performance of the Hyproc Corporation, with measuring this effect using the "T" test and simple linear regression. We have concluded that component depreciation had a negative impact on the results chart of the Hyproc Corporation, as the increase in component depreciation provisions reduced the operating result, the normal result before taxes and the net result, and raised the tax savings and the ability of self-financing. And by conducting a "T" test for two correlated samples of the averages of the financial ratios of component depreciation and previous depreciation at the significance level of 0.05, we find that the component depreciation reduced the financial, economic and commercial profitability, the operating result margin and the normal result margin before taxes, and the significance of these differences is statistically significant. By conducting a simple linear regression of the effect of component depreciation, which is expressed in the change in the depreciation allowances for vehicles compared to the previous depreciation on financial ratios and at the significance level of 0.05, we find a statistically significant inverse relationship of the impact of component depreciation on commercial and economic profitability, the margin of operating result, the margin of normal result before taxes,the financial structure of assets, and the relationship Inverse is not statistically significant on financial return.